Explaining Channel Catfish Population Characteristics in Ohio Reservoirs. (4th May 2021) - Tyszko, Stephen M.; Pritt, Jeremy J.; Conroy, Joseph D.
Abstract: North American fisheries management agencies commit considerable resources to managing reservoir fisheries for Channel Catfish Ictalurus punctatus, which often includes stocking. However, Channel Catfish population characteristics often vary greatly among reservoirs, resulting in variable and unpredictable fishery quality. We sampled Channel Catfish populations in 44 Ohio reservoirs with tandem, baited hoop nets to understand relationships among population characteristics (density, as CPUE from hoop nets; growth, as mean length at age 7; mortality, as total annual mortality from catch‐curve analysis; and size structure, as proportional size distribution), stocking, and the relationships between these characteristics and reservoir size (as surface area), predator density (as Largemouth Bass Micropterus salmoides electrofishing CPUE), and productivity (as chlorophyll‐ a concentration). We used multiple linear regression and an information theoretic approach to select the most parsimonious models for explaining observed variation in Channel Catfish density, growth, mortality, and size structure. We found that population density varied greatly among our study reservoirs, and none of our models sufficiently explained variation in density. Reservoir size and the interaction between reservoir size and population density explained the most variation in Channel Catfish growth, but productivity was also important. Small reservoirs (≤101 ha) had low to moderate densities and growth was uniformly slow; however, in larger reservoirs, lower densities resulted in faster growth. Growth increased as productivity increased. Total annual mortality was uniformly low (<0.26) but increased with density. Faster growth led to populations with larger size structures. These outcomes show that the largest Ohio reservoirs (≥406 ha) are the most suitable for supporting populations with fast growth and large size structures. Dense populations (CPUE > 50 Channel Catfish/net set) resulted in slower growth, greater mortality, and poor size structure. Future research to understand natural recruitment in reservoir Channel Catfish populations could be important for explaining variation in density.